Dampak terapeutik Peperomia Pellucida terhadap kerusakan histologis ginjal akibat paparan asap rokok pada tikus - Wardhani, Mira Kusuma; Idrus, Muhamad Firmansyah (Borobudur Nursing Review, 2025)
Chronic Kidney Disease (CKD) is a growing health problem in many countries. One of the main causes of CKD is cigarette smoke, which contains harmful chemicals like cadmium and nicotine. These substances can damage kidney tissue and increase the risk of kidney failure. Peperomia pellucida, a small herbal plant commonly found in tropical countries, has antioxidant and anti-inflammatory properties. It has been used in traditional medicine to treat various illnesses, including kidney problems. This study aimed to find out if Peperomia pellucida extract could help heal kidney damage caused by cigarette smoke. Twenty male rats were divided into three groups: a control group, a smoke-exposed group without treatment, and a smoke-exposed group treated with Peperomia pellucida extract. The rats were exposed to cigarette smoke for four weeks. Then, the treated group received the plant extract for another four weeks. The results showed that rats treated with the extract had less damage in their kidney tissues. The improvement was measured using the EGTI scoring method (Endothelial, Glomerular, Tubular, and Interstitial). This suggests that Peperomia pellucida may be useful as a natural and affordable treatment to protect the kidneys from damage caused by cigarette smoke, especially for people exposed to secondhand smoke